Divergent SARS‐CoV‐2‐specific T‐ and B‐cell responses in severe but not mild COVID‐19 patients. Issue 12 (16th November 2020) - Oja, Anna E.; Saris, Anno; Ghandour, Cherien A.; Kragten, Natasja A.M.; Hogema, Boris M.; Nossent, Esther J.; Heunks, Leo M.A.; Cuvalay, Susan; Slot, Ed; Linty, Federica; Swaneveld, Francis H.; Vrielink, Hans; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is the causative agent of the current coronavirus disease 2019 (COVID‐19) pandemic. Understanding the immune response that provides specific immunity but may also lead to immunopathology is crucial for the design of potential preventive and therapeutic strategies. Here, we characterized and quantified SARS‐CoV‐2‐specific immune responses in patients with different clinical courses. Compared to individuals with a mild clinical presentation, CD4 + T‐cell responses were qualitatively impaired in critically ill patients. Strikingly, however, in these patients the specific IgG antibody response was remarkably strong. Furthermore, in these critically ill patients, a massive influx of circulating T cells into the lungs was observed, overwhelming the local T‐cell compartment, and indicative of vascular leakage. The observed disparate T‐ and B‐cell responses could be indicative of a deregulated immune response in critically ill COVID‐19 patients. Abstract : T‐ and B‐cell responses are misbalanced in critically ill COVID‐19 patients compared to patients with mild or severe symptoms. CD4 + T‐cell responses in these patients are impaired qualitatively and quantitatively. BALF of ICU patients shows an influx of circulating T cells indicative of vascular leakage and lung damage.